# cosx(2cosx-1)=0

## Simple and best practice solution for cosx(2cosx-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for cosx(2cosx-1)=0 equation:

Simplifying
cosx(2cosx + -1) = 0
Reorder the terms:
cosx(-1 + 2cosx) = 0
(-1 * cosx + 2cosx * cosx) = 0
(-1cosx + 2c2o2s2x2) = 0
Solving
-1cosx + 2c2o2s2x2 = 0
Solving for variable 'c'.
Factor out the Greatest Common Factor (GCF), 'cosx'.
cosx(-1 + 2cosx) = 0
Subproblem 1Set the factor 'cosx' equal to zero and attempt to solve:
Simplifying
cosx = 0
Solving
cosx = 0
Move all terms containing c to the left, all other terms to the right.
Simplifying
cosx = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(-1 + 2cosx)' equal to zero and attempt to solve:
Simplifying
-1 + 2cosx = 0
Solving
-1 + 2cosx = 0
Move all terms containing c to the left, all other terms to the right.
Add '1' to each side of the equation.
-1 + 1 + 2cosx = 0 + 1
Combine like terms: -1 + 1 = 0
0 + 2cosx = 0 + 1
2cosx = 0 + 1
Combine like terms: 0 + 1 = 1
2cosx = 1
Divide each side by '2osx'.
c = 0.5o-1s-1x-1
Simplifying
c = 0.5o-1s-1x-1Solutionc = {0.5o-1s-1x-1}`

## Related pages

is 567 a prime number49qgraph 4x 2whats the prime factorization of 52derivatives of sin2xfactor x 2 11x 242001 roman numerals80-200gcf calculator algebra6.5.5sin3x 1y8y30.625 as a percentax3 bx c 0derivative of 3 cos xprime factorization of 52greatest common factors calculatorsimplify expression calculator with stepsderivative ln 3xy 3 sin 2xln u derivativecalculator subtracting fractionsderivative of tan 3xfind the prime factorization of 390.3333 as a fractionsimplify square root of 192solve the system of equations by substitution calculatorprime factorization of 170hsartwww.cotg.comfractions adding calculatorsolve 4x 2sin5x sin3xhow to change fractions to decimalshcf calculatorgreatest common factor and least common multiple calculator1000000 in roman numeralssin5x sin3xroman numerals 100-200the prime factorization of 150sinx sin-xroman numerals 88sin5pie r squared h4x 2y 8x squared plus xwhat is the prime factorization for 132adding improper fractions calculatorv lwh solve for lwrite 0.8 as a fractionmmxx roman numerals4x 5y 10789.59fgx calculatorstep by step fraction calculatorgcf of 64factorization of 175what is the square root of 10893y 5xwhat is the prime factorization of 1023m 3000xadd fractions calculatorwhat is the prime factorization of 1602y 3x 7roman numerals x1roman numerals for 196089 in roman numeral212-32sin3x sin5xwhat is the prime factorization of 7615x 75write 0.3 as a fractionsolution of quadratic equation calculator3x 4y 101972 in roman numeralscalculator to solve fractionshow to write a prime factorizationwhat is the prime factorization of 75xe x 2 derivative10.5.7cosx cosx-1 00.452 as a percent1200 in roman numeralsx2 16x987-16